2014
DOI: 10.1007/s10489-014-0614-1
|View full text |Cite
|
Sign up to set email alerts
|

Updating mined class association rules for record insertion

Abstract: Mining class association rules is an interesting problem in classification and prediction. Some recent studies have shown that using classifiers based on class association rules resulted in higher accuracy than those obtained by using other classification algorithms such as C4.5 and ILA. Although many algorithms have been proposed for mining class association rules, they were used for batch processing. However, real-world datasets regularly change; thus, updating a set of rules is challenging. This paper propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 24 publications
(53 reference statements)
1
7
0
Order By: Relevance
“…Specifically, in this study, we are interested in finding a set of association rules between two SQL query representations and use them to build an efficient classifier. Recent studies have shown that using classifiers based on class association rules resulted in higher accuracy than those obtained by using other classification algorithms such as C4.5 and ILA [29], which strengthens our motivation to evaluate CAR in our improved solution.…”
Section: Evaluating Classification Based On Association Rulessupporting
confidence: 68%
“…Specifically, in this study, we are interested in finding a set of association rules between two SQL query representations and use them to build an efficient classifier. Recent studies have shown that using classifiers based on class association rules resulted in higher accuracy than those obtained by using other classification algorithms such as C4.5 and ILA [29], which strengthens our motivation to evaluate CAR in our improved solution.…”
Section: Evaluating Classification Based On Association Rulessupporting
confidence: 68%
“…The CMAR algorithm 27 is gradually developed on the basis of the classification-based association (CBA) method. 28 The CMAR algorithm and CBA algorithm are based on the Association Rules algorithm. CMAR is the transformation method of frequent pattern (FP)-growth that evolved from CBA, which can mine association rules sets satisfying the minimum support and minimum confidence, and several strong association rules are used to determine the class label of the new sample.…”
Section: Methods Of High-voltage Switchgearsfault-influencing Factors mentioning
confidence: 99%
“…Nguyen et al [19] modified equivalence class rules tree (MECR-tree) is formed from the real dataset. While records are put in, nodes on the tree are kept up to date by altering their information comprising Obidset, count, and pos.…”
Section: Literature Reviewmentioning
confidence: 99%